PENGEMBANGAN ALAT EVALUASI PADA PEMBELAJARAN PAI - Rika, Rika; Rahimah, Rahimah; Salamah, Salamah (Berajah Journal, 2024)
Evaluation is one of the important components in the learning process, including in the subject of Islamic Religious Education (PAI). Evaluation helps teachers measure the achievement of learning objectives and identify the weaknesses and strengths of the teaching and learning process. The development of evaluation tools that are appropriate and in accordance with the characteristics of PAI subjects is a necessity to obtain accurate evaluation results and describe students' abilities comprehensively. From this background, the purpose of this study is to provide an explanation of the development of evaluation tools in PAI learning. This research is a type of library research that uses a qualitative approach with descriptive methods, the data collection technique is in the form of literature study, and the data analysis uses the content analysis method. The results showed that in this study, evaluation tools were developed in the form of authentic assessment instruments by considering the cognitive, affective, and psychomotor aspects contained in PAI subjects. This authentic assessment instrument includes project assessment, portfolio, written test, observation, and self-assessment. The development of this instrument is based on the analysis of core competencies, basic competencies, and relevant PAI materials. After going through the stages of expert validation and field trials, the authentic assessment instrument developed showed valid, practical, and effective criteria for use in measuring student learning outcomes in PAI subjects. The results of this study are expected to contribute to improving the quality of PAI learning evaluation and provide a more comprehensive picture of student achievement in cognitive, affective, and psychomotor aspects.